Periodos de tratamiento en el paciente niño - Lucía Victoria Bernal-de Jaramillo; Diana María Gaviria-Londoño (Universidad de Antioquia, 2000)
In the literature and mostly in our Faculty we ha ve a systematic. logical and complete sequence lor treating the adult petient, but we don 'tha ve any lor treating the child patient. Our purpose with this re vie w is hJl the lack 01the treatmentstages lor the child patient. Our main objetive is in the prevention lordental caries, beca use is a very important toollor perents, childs and e/inics. With a very good prevention there isno need olintervention during future stages 01trestment, being sure that wemade a velY succeslul control 01dental caries and periodontal disease.